Potensi Pembangkit Listrik Tenaga Sampah Sebagai Charging Station Kendaraan Listrik - Afifa, Mardiah (ENERGI & KELISTRIKAN, 2024)
The energy used in the transportation sector is currently still dominated by fossil fuels. As a result, the air is polluted with CO2 emissions. This CO2 problem is starting to be suppressed by the existence of electric vehicles because they are more environmentally friendly than conventional vehicles. Charging stations are needed to support the needs of electric vehicles. One of them is using a renewable waste-fired power plant as a charging station energy source. This study aims to examine the potential of a waste-powered power plant as a charging station for electric vehicles. Organic waste is the waste with the largest amount among other types of waste. As much as 3,525,320 kg/hour of organic waste can generate 30,462.31 kWh of electrical energy. So with a charging station that uses a waste power plant, it can meet the fuel needs of electric cars with a full capacity of 677 cars or can cover a distance of up to 213,236.17 km. In addition, waste power plants are more environmentally friendly and are renewable energy. So that the waste power plant has great potential as an electric vehicle charging station.